2003
DOI: 10.1002/chin.200345036
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Aminobromination of Terminal Alkenes.

Abstract: Addition reactions Addition reactions O 0060Regioselective Aminobromination of Terminal Alkenes. -Several N-Boc-2-bromoamines are prepared by a two-step method involving the reaction of new dibromocarbamate (II) with terminal alkenes to give N-bromo-N-Boc adducts, which are reduced in situ. Deprotection of these N-Boc products by treatment with HCl or TosOH affords the corresponding ammonium salts in pure state and good overall yields. The observed regioselectivity of the aminobromination for anti-Markovnikov … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The same group again described the addition of BBC to several straight and branched chain terminal alkenes, namely, styrene, 2-phenylpropene, isobutylene, 2-methylbut-1-ene, 3methylbut-1-ene, pent-1ene, hex-1-ene, hept-1-ene, oct-1-ene, and 2,4,4-trimethylpent-1-ene. 1408 All reactions were carried out in refluxing dichloromethane by adding dropwise the solution of BBC to an equimolar amount of the alkene. They observed that the addition of BBC to styrene was disturbed by relatively fast consecutive cyclization of the primarily formed N-Boc-(2-bromo-2-phenylethyl)amine to 5-phenyloxazolidin-2-one (Scheme 517).…”
Section: Zwierzak Et Al Prepared Tert-butyl Nn-dibromocarbamate (Bbc)...mentioning
confidence: 99%
See 1 more Smart Citation
“…The same group again described the addition of BBC to several straight and branched chain terminal alkenes, namely, styrene, 2-phenylpropene, isobutylene, 2-methylbut-1-ene, 3methylbut-1-ene, pent-1ene, hex-1-ene, hept-1-ene, oct-1-ene, and 2,4,4-trimethylpent-1-ene. 1408 All reactions were carried out in refluxing dichloromethane by adding dropwise the solution of BBC to an equimolar amount of the alkene. They observed that the addition of BBC to styrene was disturbed by relatively fast consecutive cyclization of the primarily formed N-Boc-(2-bromo-2-phenylethyl)amine to 5-phenyloxazolidin-2-one (Scheme 517).…”
Section: Zwierzak Et Al Prepared Tert-butyl Nn-dibromocarbamate (Bbc)...mentioning
confidence: 99%
“…The same group again described the addition of BBC to several straight and branched chain terminal alkenes, namely, styrene, 2-phenylpropene, isobutylene, 2-methylbut-1-ene, 3-methylbut-1-ene, pent-1ene, hex-1-ene, hept-1-ene, oct-1-ene, and 2,4,4-trimethylpent-1-ene …”
Section: Cohalogenation Reactionsmentioning
confidence: 99%
“…It is even possible to use a substrate such as HN(CO 2 Me)(Boc), HN(Cbz) 2 , or ethyl oxamate [EtO 2 CC(O)NHBoc] to prepare N -Boc amines (e.g. 337 ; Scheme ) in good yields after suitable deprotection. The latter nucleophile EtO 2 CC(O)NHBoc has been obtained by starting with ethyl oxamate . The trityl group also activates nitrogen in aziridine formation from 1-amino-2-alcohols, as reported by Somfai and co-workers. , Kim and Kahn have performed the Mitsunobu N -alkylation of Boc-protected amino-oxazoles and -thiazoles with lysinol and argininol to obtain reduced peptidyl azoles .…”
Section: Amines Amides (Including Nucleobases) or Azides As Nucleophilesmentioning
confidence: 99%